The impact of electron-electron correlation in ultrafast attosecond single ionization dynamics - Froebel, F. G.; Ziems, K. M.; Peschel, Ulf; Gräfe, Stefanie; Schubert, Alexander (Journal of Physics B-Atomic Molecular and Optical Physics, 2020)
The attosecond ultrafast ionization dynamics of correlated two-or many-electron systems have, so far, been mainly addressed investigating atomic systems. In the case of single ionization, it is well known that electron-electron correlation modifies the ionization dynamics and observables beyond the single active electron picture, resulting in effects such as the Auger effect or shake-up/down and knock-up/down processes. Here, we extend these works by investigating the attosecond ionization of a molecular system involving correlated two-electron dynamics, as well as non-Adiabatic nuclear dynamics. Employing a charge-Transfer molecular model system with two differently bound electrons, a strongly and a weakly bound electron, we distinguish different pathways leading to ionization, be it direct ionization or ionization involving elastic and inelastic electron scattering processes. We find that different pathways result in a difference in the electronic population of the parent molecular ion, which, in turn, involves different subsequent (non-Adiabatic) postionization dynamics on different time scales.
CRIS-Team Scopus Importer:2023-04-20
Keywords: photoemission; single-photon ionization & excitation; ultrafast phenomena